Highly efficient adsorption of dyes by biochar derived from pigments-extracted macroalgae pyrolyzed at different temperature - Chen, Yi-di; Lin, Yen-Chang; Ho, Shih-Hsin; Zhou, Yan; Ren, Nan-qi (Bioresource technology, 2018)
•Macroalgae residue is promising raw material for producing biochar.•Biochar derived from pigments-extracted macroalgae is a promising adsorbent.•The malachite green adsorption capacity of MDBC800 is 5306.2 mg/g. Biochar is known to efficiently adsorb dyes from wastewater. In this study, biochar was derived from macroalgae residue by pyrolysis, and the influence of varying temperature (from 400 °C to 800 °C) on biochar characteristics was investigated. Among the biochar samples tested, macroalgae-derived biochar possessing highly porous structure, special surface chemical behavior and high thermal stability was found to be efficient in removing malachite green, crystal violet and Congo red. The biochar derived by pyrolysis at 800 °C showed the highest adsorption capacity for malachite green (5306.2 mg g−1). In this study, the transformation of microalgae residue into a highly efficient dye adsorbent is a promising procedure for economic and environmental protection.